Regional centrality: How much is economics and how much is geography? - Crespo, N.; Fontoura, M. P.; Simões, N. (Handbook of research on the empirical aspects of strategic trade negotiations and management, 2021)
The theme of regional centrality, more commonly known as accessibility, has been increasingly invoked in recent years, mainly due to a clearer understanding that proximity to the markets is a key determinant of the location of firms. This chapter improves the most standard accessibility index using a decomposition method that allows considering the influence of (1) internal and external factors and (2) economic and geographical aspects. Each component identified has a specific interpretation and allows the identification of policy recommendations, such as the development of the transport and communication networks and active interventions to attract investment. The baseline decomposition method is adjusted in order to incorporate differences in spatial terms among the regional units considered. In order to illustrate the proposed methodology, the authors consider 171 countries. Results lead to the conclusion that the centrality level of the countries analyzed derives from different sources. Therefore, different countries may require different policy interventions to improve their centrality.